A Case Study: Murotal Distraction to Reduce Pain Level among Post-Mastectomy Patients - Suhanda; Henri Setiawan; Heri Ariyanto; Windi Oktavia (Alta Dharma Publisher, 2021)
Carcinoma mammae or breast cancer is a malignant disease that originates from the parenchyma. Women who suffer from this disease will choose treatment using mastectomy. Mastectomy treatment is a process of removing all breast tissue that can inhibit the development of cancer cells. Post-operative mastectomy pain can be relieved by non-pharmacological therapy, one of which is murotal therapy. This case study aims to present the results of applying evidence-based murotal treatment to reduce pain scales in post-mastectomy surgery patients. Physical examination was performed using the head-to-toe method in post-operative patients. The North American Nursing Diagnosis Association is used to determine nursing diagnoses. Meanwhile, nursing intervention refers to the Nursing Intervention Classification and Nursing Outcome Classification. The intervention was carried out in five stages of evidence-based nursing implementation in nursing practice, with complementary therapy in murotal therapy and progressive application for 6 days for post-mastectomy surgery patients. As a result, giving murotal therapy intervention for 6 days showed a reduction in the pain scale from a scale of 4 (1-10) to 1 (1-10). The implementation of EBN murotal therapy proved to be effective in reducing the intensity of the pain scale in post-mastectomy surgery patients